2024
DOI: 10.3390/biomedicines12030491
|View full text |Cite
|
Sign up to set email alerts
|

The Gastric Cancer Immune Prognostic Score (GCIPS) Shows Potential in Predicting an Unfavorable Prognosis for Gastric Cancer Patients Undergoing Immune Checkpoint Inhibitor Treatment

Yanjiao Zuo,
Hao Sun,
Hongming Pan
et al.

Abstract: (1) Background: This study aims to explore the predictive capability of the Gastric Cancer Immune Prognostic Score (GCIPS) for an unfavorable prognosis in gastric cancer patients undergoing immune checkpoint inhibitor (ICI) treatment. (2) Methods: This study included 302 gastric cancer patients who underwent treatment with ICIs at our institution from January 2017 to December 2022. The patients were randomly divided into a test set (201 cases) and a validation set (101 cases) using a random number table. Kapla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In conclusion, nomograms that integrate the GCIPS demonstrated excellent precision in both the validation and test sets. Furthermore, the nomograms showed that the TNM stage was not the only component with a lower predictive value than the GCIPS [ 54 ].…”
Section: Immunological Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, nomograms that integrate the GCIPS demonstrated excellent precision in both the validation and test sets. Furthermore, the nomograms showed that the TNM stage was not the only component with a lower predictive value than the GCIPS [ 54 ].…”
Section: Immunological Factorsmentioning
confidence: 99%
“…-FCGR3A-type and CD14-type macrophages were identified using single-cell data to help predict the prognosis and response to immunotherapy in patients with STAD [50] -LINC00862 may be a prognostic and diagnostic biomarker [51] patients with lower risk scores for both PD-1+ and cytotoxic T lymphocyte antigen4+ showed greater sensitivity to immunotherapy [52] the prediction signature of the pathomics-driven ensemble model continued to be an independent predictor for progression-free survival in patients with GC who underwent immunotherapy [53] -GCIPS is an independent predictive factor for both PFS and OS [54]…”
Section: Immunological Predictive Factors Of Immunotherapy In Gastric...mentioning
confidence: 99%